Human Resource Transformation In The Digital Era: The Influence Of Competence, Human Resource Communication, And Responsiveness On The Service Image Of Lppjphki Universitas Dehasen Bengkulu - Vettyca Diana Saputri; Anzori Anzori; Dodi Hardinata (UNIVED Press, 2026)
This study aims to examine Human Resource Transformation in the Digital Age: The Influence of Competency, Human Resource Communication, and Responsiveness on the Service Image of LPPJPHKI Unived Bengkulu. The focus of this study is to determine whether Competency, Human Resource Communication, and Responsiveness influence the Service Image of LPPJPHKI Unived Bengkulu. The approach used is a quantitative approach with primary data. The sample in this study consists of respondents who meet the specified characteristics, totalling 146 participants. The results of the multiple linear regression analysis yielded the equation Y = 7.570 + 0.452 X1 + 0.282 X2 + 0.094 X3 + e. This indicates a positive regression direction, meaning that the variables of Competency, Human Resource Communication, and Responsiveness have a positive influence on the Service Image of LPPJPHKI Unived Bengkulu. From the calculations using SPSS 25, the coefficient of determination (R-squared) is found to be 0.590. This means that the values of Competency (x1), Human Resource Communication (x2) and Responsiveness (x3) account for 59% of the variation in Service Image (Y), whilst the remaining 41% is influenced by other variables not examined in this study. The results of the t-test at a significance level of < 0.05 indicate that, individually, Competency (x1), Human Resource Communication (x2) and Responsiveness (x3) have a significant influence on Service Image (Y) at LPPJPHKI Unived Bengkulu. As the F-test result is less than 0.000, the variables Competency (x1), Human Resource Communication (x2) and Responsiveness (x3) have a significant influence on Service Image (Y) at LPPJPHKI Unived Bengkulu.